THE CORRELATION BETWEEN STUDENTS’ SELF-CONFIDENCE AND SPEAKING ACHIEVEMENT - Fitri Novia; Rachmanita; Rika Ramayanti (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Students should be relaxed and confident while using English as they are expected to be bolder than ever while sharing their thoughts or ideas and speaking in front of big audiences. In order to boost their confidence and make language learning easier, learners must understand how their self-confidence affects their ability to learn a language. The goal of the study was to determine whether or not there was a link between students’ speaking proficiency and their confidence in the tenth grade at UPT SMA Negeri 06 Ogan Ilir. The study participant was all the tenth-grade students of UPT SMA Negeri 06 Ogan Ilir. The sample of the study consisted of 124 pupils chosen by using total sampling. This study was conducted using a correlation research approach. The questionnaire and oral test were both utilized to gather the data. The Pearson Product Moment correlation analysis was employed for analyzing the data. Based on the findings, it was discovered that the correlation coefficient of r-obtained (0.274), at p-value: 0.0020.05, and it was greater than r-table (0.176). It implied that speaking proficiency and student self-confidence were related. It was evident that students' self-confidence played a significant role in earning a high speaking achievement score.